ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI INDEKS HARGA SAHAM DI INDONESIA - Soebagiyo, Daryono; Prasetyowati, Endah Heni (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2003)
Since 1998, Indonesia capital market experiencing rapid development, go public activity in stock exchange and stock trading activity getting crowded. People interest observes monetary factors such as money circulation, deposit interest, foreign currency exchange, and inflation that predicted affecting compound stock index in Jakarta stock exchange from 1998 to 2002. Time series data from 1998-2002 gained from published issues like financial statement Indonesian Bank, Body of Statistic Center, and other sources. This research using adaptive expectation model analysis tools, that is rationalization model proposed by Nerlove, as stock adjustment model or partial adjustment model (PAM). Use of this model bring advantage in short and long term analysis.